Women’s aspirations for the future, and their financial, social and educational investments - Raghunathan, Kalyani; Quisumbing, Agnes R.; Kumar, Neha; Cunningham, Kenda (International Food Policy Research Institute, 2018)
We examine the correlates of aspirations of rural women around income, asset ownership, social status and the education of their children, using primary data from India. We then investigate how the gaps between current and aspired-to status are associated with individual investments in financial, social status-related, and educational dimensions.